2014
DOI: 10.4161/15384101.2014.953424
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 K27 acetylation marks a potent enhancer element on the adipogenic master regulator gene Pparg2

Abstract: PPARγ2 is expressed almost exclusively in adipose tissue and plays a central role in adipogenesis. Despite intensive studies over the last 2 decades, the mechanism regulating the expression of the Pparg2 gene, especially the role of cis-regulatory elements, is still not completely understood. Here, we report a comprehensive investigation of the enhancer elements within the murine Pparg2 gene. Utilizing the combined techniques of sequence conservation analysis and chromatin marker examination, we identified a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…5A]. At differentiating day 2, just before Pparγ2 is initially induced, analysis of specific acetylation marks also reveals a marked decrease in H3K27Ac (a key marker of active enhancers during adipogenesis32 ) in Rictor-iKO PBA , Akt1-iKO PBA , and Acly-iKO PBA cell lines [Supplementary Fig. 5B-D].…”
mentioning
confidence: 99%
“…5A]. At differentiating day 2, just before Pparγ2 is initially induced, analysis of specific acetylation marks also reveals a marked decrease in H3K27Ac (a key marker of active enhancers during adipogenesis32 ) in Rictor-iKO PBA , Akt1-iKO PBA , and Acly-iKO PBA cell lines [Supplementary Fig. 5B-D].…”
mentioning
confidence: 99%
“…Depletion of CBP/p300 with ribozyme strongly represses the expression of PPARγ-targeted genes and thus attenuates adipogenic differentiation of preadipocytes [115]. Furthermore, studies on the mechanism of p300-mediated histone modification have revealed that p300 binds to Pparg2 promoter and enhancer regions with enhanced H3/H4ac and H3K27ac, respectively [116,117]. GCN5 and PCAF have also been reported to be involved in MSC adipogenic differentiation.…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Histone acetylation and deacetylation are catalyzed by HATs and HDACs, respectively (39,(41)(42)(43)(44). In general, multiple lysine residues on histones 3 and 4 are acetylated during transcriptional activation (i.e., H3K9, H3K14, H3K18, H3K23, H3K27, H3K56, and H4K5, H4K8, H4K12, H4K16) (40,42,43,(45)(46)(47). During this process, HATs catalyze the transfer of the acetyl group from acetyl-CoA onto FIGURE 1 | The different types of adipocytes, and HATs/HDACs that regulate brown adipogenesis and adaptive thermogenesis.…”
Section: Overview Of Histone Acetylation and Deacetylationmentioning
confidence: 99%